Case Report: Pelvic mass and massive ascites as the first symptom in cervical adenocarcinoma: report of two cases and literature review - Yuan, Mingwei; Zhang, Yan; Wang, Kana; Xi, Mingrong (Frontiers in Oncology, 2023)
Cervical adenocarcinoma accounts for 10%–25% of total cases of cervical carcinoma. But in recent years, the incidence of adenocarcinoma has risen both proportionally and absolutely. Clinically, most cervical adenocarcinoma show no symptom or present with abnormal uterine bleeding or vaginal discharge, similar to squamous cell carcinoma. What different about it is that cervical cytological testing demonstrates a high false-negative rate of cervical adenocarcinoma, potentially leading to the failure in detecting in early stage. This report presents two cases both with pelvic masses, and massive ascites served as the initial symptom, which is similar to the clinical symptom of ovarian cancer, but ultimately diagnosed with cervical adenocarcinoma through surgical specimens. There are few literature reports on this situation. Hence, a literature review also has been performed to improve the recognition for cervical adenocarcinoma presenting with pelvic masses and massive ascites, and to avoid misdiagnosis.